Pulmonary artery banding in congenital heart disease associated with pulmonary hypertension. Issue 4 (July 1968) - Reid, J. M.; Barclay, R. S.; Coleman, E. N.; Stevenson, J. G.; Welsh, T. M.; McSwan, N.
Abstract : A report is presented of pulmonary artery banding in 45 children with congenital heart disease associated with severe pulmonary hypertension. The majority were in uncontrollable heart failure and were in the age group 3 to 18 months. Nine older children not in heart failure were operated on because of serious pulmonary hypertension associated with malformations considered unsuitable for complete repair (truncus arteriosus, single ventricle). The mortality in those with uncomplicated ventricular septal defect was low (5.5%), but was much higher in those with accompanying lesions or more complex abnormalities (63%). All have been under supervision since operation and most have improved with diminution in cardiac size and recession of pulmonary congestion. Two have been recatheterized and both have undergone successful closure of their ventricular septal defect. It is our intention to reinvestigate many of the others three to four years after banding to assess the size of the defect prior to further surgery.